GTM-CSec: Game theoretic model for cloud security based on IDS and honeypot. Issue 92 (May 2020) - Gill, Komal Singh; Saxena, Sharad; Sharma, Anju
Highlights: The rapid increase in the IoT devices pose more threat to the cloud. The proposed model (GTM-CSec) helps the detection system comprising of IDS and Honeypots to intelligently detect attacks. A non-cooperative game has been designed between the attacker and the defender and various strategies have been delineated. The proposed model intelligently selects the particular module out of the signature, anomaly, and honeypot based detection. This reduces energy consumption and increases the overall security and efficiency. A mixed strategy Nash Equilibrium and simulation results conclude the game model. Abstract: Cloud Computing has been adopted by many leading organizations for storage, processing, sharing and to provide other services. It faces several security challenges from its surroundings in terms of regular and sophisticated attacks. These challenges become worse when the Internet of Things (IoT) devices are connected to it. This is because of their low-security characteristics. These threats are generally handled using techniques such as Intrusion Detection System (IDS), Honeypots, Firewall, etc. To identify the best defense strategy in these techniques, further research is needed. Hence in this paper, a game-theoretic model GTM-CSec has been proposed. The proposed model intelligently selects the most suitable module out of the signature, anomaly, and honeypot based detection to detect the attack. The selection of a particular detection module instead of using all in parallel not only leads to the reduction of energy consumption but also increases the overall efficiency of the defender system. The strategies for both the defender and attacker have been evaluated and the best one has been delineated with Nash Equilibrium (NE). The simulation results prove that with the introduction of the proposed model, the defender system is very effective against the attacker.